(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In the technique of percutaneous endoscopic lumbar discectomy (PELD), access to the disc is achieved through Kambin’s triangle, formed by the exiting nerve root (hypotenuse), the superior endplate of the caudal vertebra (base), and the superior articular process of the caudal segment (height). The PELD procedure involves removing the nucleus pulposus using forceps within the annulus fibrosus, thus being considered an "inside-out" technique, which complicates the removal of a migrated disc herniation [1,2,3]. During the PELD technique, foraminoplasty is performed using sequential trephines, followed by the insertion of an endoscope into the spinal canal to remove herniated material. Thus, PELD is regarded as an "outside-in" technology, providing significant advantages for treating highly migrated disc herniations and lumbar spinal stenosis [4,5,6,7]. Regarding the L5/S1 segment, puncture through the foraminal opening can be technically challenging due to the high iliac crest, large L5 transverse process, and concealed location of the herniated material. In such cases, the interlaminar approach may be a more preferable option [8,9].